Impact of Co-operativisation on Working Conditions Study of Beedi Industry in Kerala - M Mohandas P V Praveen Kumar (Economic and Political Weekly June 27, 1992, 1992)
Wage and non-wage benefits of workers in Beedi workers' co-operatives have improved with the creation of such co-operatives. While there is considerable disparity in the benefits of co-operative and contract workers, the presence of the former has influenced some improvements in contract workers' benefits